MDSC depletion during immunization with heat-killed Mycobacterium tuberculosis increases protection against BCG infection - Aintablian, Arpa; Arold, Anna M.; Alattar, Haisam; Cyran, Laura; Schoen, Christoph; Du Plessis, Nelita; Walzl, Gerhard; Schaible, Ulrich; Beilhack, Andreas; Nieuwenhuizen, Natalie E.; Lutz, Manfred B. (Frontiers in Immunology, 2025)
Tuberculosis (TB) remains one of the deadliest infectious diseases globally. Although the approved human Bacille-Calmette-Guérin (BCG) vaccines provide limited protection, a vaccine based on Mycobacterium tuberculosis (Mtb) has yet to be approved. Our previous findings demonstrated that s.c. immunization with heat-killed Mtb significantly increased the number of monocytic myeloid-derived suppressor cells (M-MDSC) in mice. Thus, we hypothesized that the defense against a subsequent BCG infection would be compromised in Mtb-immunized mice. Surprisingly, mice vaccinated with Mtb were protected against BCG infection and exhibited elevated frequencies and activation of dendritic cells (DC) and mycobacteria-specific T cells, despite high frequencies and suppressor activity of M-MDSC. Genetic ablation of CCR2+ monocytic cells or pharmacological intervention with all-trans retinoic acid (ATRA) reduced the frequency of Mtb-induced M-MDSC, enhanced the frequencies and activation of DC and CD4+ T cells, and resulted in decreased bacterial loads in the lungs and spleen. These findings provide new insights into TB vaccination using heat-killed Mtb despite the concurrent unwanted effects of vaccine-induced M-MDSC. M-MDSC depletion via ATRA further shifts the balance toward immunity and should be considered an adjunct host-directed therapy alongside TB vaccines in humans.